Acute Coronary Syndrome Multidisciplinary and Pathway-Based Approach - Hong, Mun K.; Herzog, Eyal (Springer London : Imprint: Springer, 2008)
Acute coronary syndrome (ACS) affects millions of patients annually and requires immediate diagnosis and therapy. Critically, given the aging global population, ACS is set to become an even greater medical problem, not only for the emergency room and cardiology physicians, but for all specialists treating the older population at risk of ACS. Advances in the treatment of ACS can justifiably be considered one of the great achievements of modern medicine. The evolution of treatment strategies represents a remarkable achievement, but there is an urgent need to educate those specialists treating the high-risk population. This practical algorithm-based handbook addresses the diagnosis and treatment of these patients and is designed for the medical personnel involved in the triage and management of ACS patients. Acute Coronary Syndrome: Multidisciplinary and Pathway-Based Approach offers clinical assistance to all trainees and non-medical specialists and provides a framework for more experienced staff to manage ACS patients effectively. The authors have compiled a wealth of clinically useful tools and information drawn from their experience at St. Luke's-Roosevelt Hospital Center in New York, making this book a comprehensive evidence-based resource that allows readers to expand their knowledge and enables rapid diagnosis and treatment of patients with ACS.